Cyanine dyes in the mitochondria-targeting photodynamic and photothermal therapy - Kejík, Zdeněk; Hajduch, Jan; Abramenko, Nikita; Vellieux, Frédéric; Veselá, Kateřina; Fialová, Jindřiška Leischner; Petrláková, Kateřina; Kučnirová, Kateřina; Kaplánek, Robert; Tatar, Ameneh; Skaličková, Markéta; Masařík, Michal; et al. (Communications chemistry, 2024)
Mitochondrial dysregulation plays a significant role in the carcinogenesis. On the other hand, its destabilization strongly represses the viability and metastatic potential of cancer cells. Photodynamic and photothermal therapies (PDT and PTT) target mitochondria effectively, providing innovative and non-invasive anticancer therapeutic modalities. Cyanine dyes, with strong mitochondrial selectivity, show significant potential in enhancing PDT and PTT. The potential and limitations of cyanine dyes for mitochondrial PDT and PTT are discussed, along with their applications in combination therapies, theranostic techniques, and optimal delivery systems. Additionally, novel approaches for sonodynamic therapy using photoactive cyanine dyes are presented, highlighting advances in cancer treatment.